ANALISIS ORGANOLEPTIK PADA PENGEMBANGAN OLAHAN PANGAN BERBASIS WORTEL DI KELOMPOK WANITA TANI DI DESA TEMANGGUNG KABUPATEN MAGELANG - Alfina Handayani; Rosidah Rosidah (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2017)
Temanggung Village is a carrot-producing village, meanwhile the number of carrots waste is still high. This condition because of farmers in this area lack of knowledge and technology to processing carrot. This study aims to determine the type of processed carrot-based which has the organoleptic properties favored by the panelists. Processed foodswere noodles, dodol, sticks, carrot juice and toffee. The study involved 18 untrained panelists who were members of the farmer group. The results showed Dodol is a type of processed carrot-based most favored by panelists, with a color score of 3.7, flavors 3.2, aroma 3.4, texture 3.1 and overall has a score of 3.4 compared to other processed products such as sticks, tofi , instant drinks and noodles.Need improvement of carrot noodles especially from the texture to be more acceptable.